Characterization of anti-drug antibody responses to the T-cell engaging bispecific antibody cibisatamab to understand the impact on exposure - Lotz, Gregor P.; Lutz, Achim; Martin-Facklam, Meret; Hansbauer, Andre; Schick, Eginhard; Moessner, Ekkehard; Antony, Michael; Stuchly, Thomas; Viert, Maria; Hosse, Ralf J.; Freimoser-Grundschober, Anne; Klein, Christian; et al. (Frontiers in Immunology, 2024)
An appropriately designed pharmacokinetic (PK) assay that is sensitive for anti-drug antibody (ADA) impact on relevant exposure is an alternative strategy to understand the neutralizing potential of ADAs. However, guidance on how to develop such PK assays and how to confirm functional ADA impact on exposure is missing. Here, the PK assay of a T-cell-engaging bispecific antibody, cibisatamab, was developed based on its mechanism-of-action (MoA). Using critical monoclonal anti-idiotypic (anti-ID) antibody positive controls as ADA surrogates, the impact on exposure was evaluated pre-clinically. In a phase I clinical trial (NCT02324257), initial data suggest that the combination of ADA and PK assay allowed for correlation of the ADA response with cibisatamab exposure. To understand neutralizing potential of patient-derived ADAs on drug activity, advanced ADA characterization has been performed. Structural binding analysis of ADAs to antibody domains of the drug and its impact on targeting were assessed. For this purpose relevant patient ADA binding features were identified and compared with the specific monoclonal anti-ID antibody positive controls. Comparable results of target binding inhibition and similar impact on exposure suggest that the observed reduction of Cmax and Ctrough level in patients is caused by the neutralizing potential of ADAs and allows a correlation of ADA response and loss of exposure. Therefore, the described study provides important functional aspects for the development of an appropriately designed PK assay for bispecific antibodies as an alternative option towards the understanding of neutralizing ADA impact on exposure.